The therapeutic alliance and dropout in cognitive behavioral therapy of depression. (17th November 2022) - Murphy, Samuel T.; Garcia, Ramiro A.; Cheavens, Jennifer S.; Strunk, Daniel R.
Abstract : Objective: : Identifying predictors of dropout is an important step in improving treatment outcomes. The alliance is the most frequently studied psychotherapy process variable, but its relation to dropout in cognitive behavioral therapy (CBT) of depression is not well understood. Methods: : We evaluated the alliance at session one as reported by clients and therapists as predictors of dropout among 126 clients with major depressive disorder participating in CBT for depression. Results: : Over a similar time period, those who dropped out experienced less symptom change than those who did not. Client, but not therapist reported alliance was related to reduced risk for dropout. This relation remained significant even when clients' pre-treatment predictions of the alliance were included as a covariate. Concurrent use of medication did not moderate the alliance-dropout relation. Conclusion: : Our findings are consistent with alliance being an important contributor to risk of dropout in CBT for depression. Future research should investigate intervention strategies that might promote the alliance as a means of reducing dropout.